Review of the effects of technical assistance on program, organization and system change - Carl J. Dunst; Kimberly Annas; Helen Wilkie; Deborah W Hamby (Institute of Advanced Engineering and Science, 2019)
Findings from a synthesis of technical assistance models and frameworks were used to code the use of 25 core elements of technical assistance in studies and evaluations of implementation interventions to affect program, organization, and systems change. The 25 core elements were group into five components: preparation for the provision of technical assistance, development of a technical assistance plan, implementation of technical assistance, evaluation of the effects of technical assistance, and sustainability of technical assistance-facilitated changes. Results indicated that a subset of 11 core elements was related to between groups and between condition differences in the sizes of effect for program, organization, and systems changes. Results also showed that more intensive technical assistance was associated with larger sizes of effects compared to less intensive technical assistance and that particular combinations of practices were associated with the largest sizes of effect.